Design of MIMO and MU-MIMO Antennas for Modern High Data Rate Wireless Systems - Saluja, Deepak (My University, 2015)
The trends in wireless communication are changing day by day. To meet the challenges of modern day wireless systems, the multiple input multiple output (MIMO) antennas are proposed in the report. The high data rate requirement for modern day wireless system makes it necessary to adopt MIMO systems. The size of the device is another constraint after data rate of the systems. The planar antennas proved as revolution in the antenna design enables achievement in terms of size reduction and conformal nature of antenna. The MIMO planar antennas are quite desirable for the reason. The literature survey is presented in context of MIMO systems. The different type of MIMO antennas are discussed by authors in the literature. The various methods are presented by the authors in literature to increase isolation between the antenna elements so to decrease correlation coefficient and to increase the data rate. The planar MIMO antennas are characterized by specific parameters other than the parameters used in context of antenna design. The planar antennas are characterized by the parameters like Scattering parameters, Coupling coefficient, Isolation, Correlation coefficient, ECC (Envelope correlation coefficient), Mean effective gain (MEG) and branch power ratio etc. The planar MIMO antennas can be understand as evolution of planar antennas from rectangular Microstrip patch antenna. In this study, the MIMO antennas are presented evolving from the simple microstrip patch antenna. The data rate of system depends on the correlation between different antenna elements in MIMO systems. The simple rectangular planar antenna is designed and matching is achieved by inset feed. The designed antenna resonates at 2.4 GHz in the dominant mode. The gain for the proposed antenna is also discussed. After design of antenna element the MIMO system is proposed and analyzed. The value of S11, S12 is calculated and the gain parameter is also presented in the report for the proposed MIMO systems.
ME, ECED
Keywords: MIMO Antennas; ECC,LTE,TARC; ECED